Impact of Social Media on Adolescents. Issue 2 (March 2022) - Beal, Judy A.
Abstract : Recent evidence suggests social media can have a negative effect on adolescents. Whistle-blower testimony before the United States Congress in Fall 2021 emphasized the knowledge that social media companies have about these effects and their lack of action to make their platforms safer for adolescents. Our pediatric nursing expert, Dr. Beal, covers this controversy and how pediatric nurses can help parents promote better use of social media for their children.